Occupational justice health questionnaire: reflections on its application/ Questionário de saúde e justiça ocupacional: reflexões em sua aplicação - Sy, Michael Palapal; Roraldo, Ma. Patricia Nicole Ragunton; Delos Reyes, Rod Charlie Razon; Yao, Daryl Patrick Gamboa; Pineda, Roi Charles Sarmiento (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: Occupational justice concept is defined as the equal access and participation in all occupations, including the resources required for participation and opportunities for social inclusion. Occupational justice not only remains conceptually ambiguous for occupational therapy practice but also lacks critical examination of its applicability to non-Western cultures. Objective: This article describes the reflexive process exercised by the researchers during and after using the Occupational Justice Health Questionnaire (OJHQ) as an occupational therapy tool in a substance addiction rehabilitation setting in the Philippines. Method: This qualitative study gathered transcriptions from field notes and focus group discussions of the authors. These transcriptions were characterized by the authors’ reflections on their experiences using the OJHQ on four distinct periods: 1) OJHQ translation, 2) pilot testing, 3) OJHQ-Filipino version administration, and 4) project conclusion. Data were analyzed through thematic analysis. Results: Qualitative data revealed four themes: tool usefulness; administration guidelines; contextualized use of the tool; and nuances of occupational injustices in substance addiction and rehabilitation setting. Conclusion: Findings expanded OJHQ’s purpose to enhance clinical reasoning, promote justice-oriented health care, activate reflective practice, and recognize the interweaving and evolving nature of injustices. This article offers an understanding of how reflections can facilitate cultural adaptation of practice tools used in occupational therapy and justice practice.